Arbuscular Mycorrhizae Contribute to Growth, Nutrient Uptake, and Ornamental Characteristics of Statice (Limonium sinuatum [L.] Mill.) Subject to Appropriate Inoculum and Optimal Phosphorus - Sheikh-Assadi, Morteza; Khandan-Mirkohi, Azizollah; Taheri, Mohammad Reza; Babalar, Mesbah; Sheikhi, Hossein; Nicola, Silvana (Horticulturae, 2023)
With the world’s population and pollutants on the rise, it is crucial to find sustainable and environmentally friendly solutions that increase production efficiency. Organic horticulture is an effective strategy for creating a harmless and sustainable crop production system. Arbuscular mycorrhizal fungi (AMF) have been proposed as reliable biofertilizers for sustainable agriculture, and inoculum production is a rapidly expanding market. AMF can enhance plant nutrition and growth, but their efficacy varies depending on the plant species, inoculum type, and available P concentrations. This study evaluates the response of ornamental statice (Limonium sinuatum [L.] Mill.) to mycorrhizal inoculation (first factor) with Glomus mosseae (M1), G. intraradices (M2), or their mixture (M3), plus non-inoculation (M0), and varying available P concentrations (second factor) of 10 (control, P1), 20 (P2), and 40 (P3) mg kg−1 soil in greenhouse conditions in a factorial experiment based on randomized complete block design with three replications. Root colonization, growth parameters, some ornamental traits, and the absorption of P, N, K, Ca, Zn, and Fe were measured. Root colonization was estimated as 30–65% and was reduced approximately by 32.4% with increasing P concentration in the soil. The lowest colonization percentage was recorded in P3 (45.69, 39.31, and 30.18 for M1, M2, and M3, respectively). Statice plants were positively influenced by inoculation, especially with G. mosseae in moderately available P (P2), which was also confirmed by the results of the principal component analysis. Overall, inoculated plants exhibited better nutritional status, growth, and ornamental traits than non-inoculated plants. Furthermore, mycorrhization delayed the time to the flowering of statice by 12, 7, and 9 days in M1, M2, and M3, respectively, compared to non-mycorrhizal (M0) plants. In conclusion, mycorrhizal inoculation can improve the plant nutrition, growth, and ornamental value of statice by selecting appropriate inoculum and optimal P concentrations. The results of this study suggest that mycorrhizal inoculation can be effectively used in the future to increase the quantity and quality of statice production.